2019
DOI: 10.1002/slct.201900814
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation and In Silico Studies of 1,2,4‐Triazole and 1,3,4‐Thiadiazole Derivatives as Antiherpetic Agents

Abstract: Two isosteric series of 1,2,4-triazole and 1,3,4-thiadiazole derivatives were designed and synthesized in this work to be evaluated for their antiviral activity. Compounds 2-9 and 11-19 were synthesized and their antiviral activity was tested against herpes simplex virus type 1, HSV-1, using acyclovir, ACV, as a reference drug. In addition, molecular docking into the active site of HSV-1 thymidine kinase was performed to interpret the data obtained from biological testing, and all compounds were subjected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…To investigate the molecular interaction pattern by which vitexin might exert its antiviral activity, the molecular docking approach was employed. Several molecular targets commonly used for screening small molecules in the field of antiviral drug discovery such as HSV type‐1 DNA polymerase, HSV type‐1 thymidine kinase, HAV 3C proteinase, HBV capsid protein, and HCV protease‐helicase, were exploited for in silico study. A prerequisite to any successful experiment is the validation step.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the molecular interaction pattern by which vitexin might exert its antiviral activity, the molecular docking approach was employed. Several molecular targets commonly used for screening small molecules in the field of antiviral drug discovery such as HSV type‐1 DNA polymerase, HSV type‐1 thymidine kinase, HAV 3C proteinase, HBV capsid protein, and HCV protease‐helicase, were exploited for in silico study. A prerequisite to any successful experiment is the validation step.…”
Section: Resultsmentioning
confidence: 99%
“…40 ) was found to be the most potent compound, which could reduce the viral plaques by 50% at a dose of 80 μM against herpes simplex virus-1 (HSV-1), grown on Vero African green monkey kidney cells. Moreover, compound 193 possessed higher selectivity than acyclovir (>200 μM vs 80 μM) [ 172 ]. Docking studies revealed that compound 193 interacted into the active site of HSV-1 thymidine kinase mainly by making many hydrogen bonds.…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…However, 103-105 showed remarkable activity against influenza A virus, particularly the H3 N2 strain. [100] A set of 1,2,4-triazolo[5,1-c][1,2,4]triazin-7-ones bearing substituents at 4 positions of the heterocycle that mimic the nucleoside's glycoside moiety (106)(107)(108)(109)(110)(111) was synthesized, and their antiviral activity against herpes simplex virus 1 (HSV-1) was assessed (Figure 35). Compounds with 2-hydroxy-ethoxymethyl functionality 106-108 inhibited the virus replication by 50 percent at concentrations higher than 250 μM.…”
Section: Acyclic Nucleoside Bridgehead 124-triazolesmentioning
confidence: 99%
“…It is noteworthy that the antiviral activity was dramatically decreased by changing the side chain at 6 positions, from chloroethyl in 129 to ethoxycarbonyl 130 ( Figure 42). [110] Liu and colleagues designed and synthesized a series of bridgehead nitrogen 1,2,4-triazolo[1,5-a]pyrimidine heterocycles (131-137) as powerful HIV-1 NNRTIs (Figure 43). Most of these new congeners demonstrated good to excellent activity against wild-type HIV-1 IIIB virus.…”
Section: Non-nucleoside Bridgehead 124-triazolesmentioning
confidence: 99%
See 1 more Smart Citation